Time-of-Day Effects on Metabolic and Clock-Related Adjustments to Cold - Machado, Frederico Sander Mansur; Zhang, Zhi; Su, Yan; de Goede, Paul; Jansen, Remi; Foppen, Ewout; Coimbra, Cândido Celso; Kalsbeek, Andries (Frontiers in Endocrinology, 2018)
Background. Daily cyclic changes in environmental conditions are key signals for anticipatory and adaptive adjustments of most living species, including mammals. Lower ambient temperature stimulates the thermogenic activity of brown adipose tissue and skeletal muscle. Given that the molecular components of the endogenous biological clock interact with thermal and metabolic mechanisms directly involved in the defense of body temperature, the present study evaluated the differential homeostatic responses to a cold stimulus at distinct time-windows of the light/dark-cycle. Methods. Male Wistar rats were subjected to a single episode of 3 h cold ambient temperature (4°C) at one of 6 time-points starting at Zeitgeber Times 3, 7, 11, 15, 19 and 23. Metabolic rate, core body temperature, locomotor activity, feeding and drinking behaviors were recorded during control and cold conditions at each time-point. Immediately after the stimulus, rats were euthanized and both the soleus and brown adipose tissue were collected for RT-PCR. Results. During the light phase (i.e., inactive phase) cold-exposure resulted in a slight hyperthermia (p<0.001). Light phase cold exposure also increased metabolic rate and locomotor activity (p<0.001). In addition, the prevalence of fat oxidative metabolism was attenuated during the inactive phase (p<0.001). These metabolic changes were accompanied by time-of-day and tissue-specific changes in core-clock gene expression, such as DBP (p<0.0001) and REV-ERBα (p<0.01) in the brown adipose tissue and CLOCK (p<0.05), PER2 (p<0.05), CRY1 (p<0.05), CRY2 (p<0.01) and REV-ERBα (p<0.05) in the soleus skeletal muscle. Moreover, genes involved in substrate oxidation and thermogenesis were affected in a time-of-day and tissue-specific manner by cold-exposure. Conclusion. The time-of-day modulation of substrate mobilization and oxidation during cold-exposure provides a clear example of the circadian modulation of physiological and metabolic responses. Interestingly, after cold exposure, time-of-day mostly affected circadian clock gene expression in the soleus muscle, despite comparable changes in locomotor activity over the L/D-cycle. The current findings add further evidence for tissue-specific actions of the internal clock in different peripheral organs such as skeletal muscle and brown adipose tissue.